GENETIC VARIABILITY AND MULTI-TRAIT SELECTION FOR SUPERIOR TRAITS IN WILD YAM HYBRIDS - Oyedoyin, Femi Patrick; Olawuyi, Odunayo J.; Agre, Paterne Angelot; Fowobaje, Kayode R.; Asfaw, Asrat (FUDMA JOURNAL OF SCIENCES, 2025)
The interspecific breeding of yams (Dioscorea spp.) for superior traits is hindered by the dioecious nature of their flowers and low flowering frequency, despite the potential of wild yams to improve related cultivated varieties. However, the genetic variability of these wild yam species has yet to be fully explored. This study investigated the genetic variability and heritability estimates for multi-trait selection of hybrids derived from crosses between two wild yam species, Dioscorea abyssinica and Dioscorea praehensilis. Field experiment was conducted on 65 hybrids using a partially replicated block design. With standard descriptors, data were collected on phenotypic traits, including stem length, internode, plant vigour, tuber length, tuber weight, tuber width, tuber thorniness, and tuber surface cracks. Heritability, genetic advance and variance components were estimated to quantify the genetic contribution to trait variability. Analysis of variance identified significant differences (p=0.00) among hybrids and high genetic variability was observed in phenotypic traits assessed, with tuber weight showing the highest genotypic (104%) and phenotypic (127%) variances. Heritability estimates suggested strong selection potential for stem length (74%), tuber weight (67%) and tuber hairiness (65%), while tuber shape (7%) and tuber width (9%) showed low genetic potential. Multi-trait Genotype Ideotype Distance Index (MGIDI) analysis further identified 8 high-performing wild yam hybrid accessions (TDabp2101010, TDabp2101013, TDabp2101030, TDabp2101042, TDabp2101046, TDabp2101050, TDabp2101052, and TDabp2101055). These findings demonstrate the potential of wild yam hybrids for trait introgression, thereby paving way for the development of new yam cultivars and providing valuable insights for yam improvement programs.